Detection and Characterization of Miniature Inverted-Repeat Transposable Elements in “Candidatus Liberibacter asiaticus” - Wang, Xuefeng (American Society for Microbiology, 2013)
Miniature inverted-repeat transposable elements (MITEs) are nonautonomous transposons (devoid of the transposase gene tps) that affect gene functions through insertion/deletion events. No transposon has yet been reported to occur in “Candidatus Liberibacter asiaticus,” an alphaproteobacterium associated with citrus Huanglongbing (HLB, yellow shoot disease). In this study, two MITEs, MCLas-A and MCLas-B, in “Ca. Liberibacter asiaticus” were detected, and the genome was characterized using 326 isolates collected in China and Florida. MCLas-A had three variants, ranging from 237 to 325 bp, and was inserted into a TTTAGG site of a prophage region. MCLas-A had a pair of 54-bp terminal inverted repeats (TIRs), which contained three tandem repeats of TGGTAACCAC. Both “filled” (with MITE) and “empty” (without MITE) states were detected, suggesting the MITE mobility. The empty sites of all bacterial isolates had TIR tandem repeat remnants (TRR). Frequencies of TRR types varied according to geographical origins. MCLas-B had four variants, ranging from 238 to 250 bp, and was inserted into a TA site of another “Ca. Liberibacter” prophage. The MITE, MCLas-B, had a pair of 23-bp TIRs containing no tandem repeats. No evidence of MCLas-B mobility was found. An identical open reading frame was found upstream of MCLas-A (229 bp) and MCLas-B (232 bp) and was predicted to be a putative tps, suggesting an in cis tps-MITE configuration. MCLas-A and MCLas-B were predominantly copresent in Florida isolates, whereas MCLas-A alone or MCLas-B alone was found in Chinese isolates.